Chemoresistance of Lung and Breast Cancer Cells Growing Under Prolonged Periods of Serum Starvation. Issue 8 (28th February 2017) - Yakisich, Juan Sebastian; Venkatadri, Rajkumar; Azad, Neelam; Iyer, Anand Krishnan V.
Abstract : The efficacy of chemotherapy is hindered by both tumor heterogeneity and acquired or intrinsic multi‐drug resistance caused by the contribution of multidrug resistance proteins and stemness‐associated prosurvival markers. Therefore, targeting multi‐drug resistant cells would be much more effective against cancer. In this study, we characterized the chemoresistance properties of adherent (anchorage‐dependent) lung H460 and breast MCF‐7 cancer cells growing under prolonged periods of serum starvation (PPSS). We found that under PPSS, both cell lines were highly resistant to Paclitaxel, Colchicine, Hydroxyurea, Obatoclax, Wortmannin, and LY294002. Levels of several proteins associated with increased stemness such as Sox2, MDR1, ABCG2, and Bcl‐2 were found to be elevated in H460 cells but not in MCF‐7 cells. While pharmacological inhibition of either MDR1, ABCG2, Bcl‐2 with Verapamil, Sorafenib, or Obatoclax, respectively decreased the levels of their target proteins under routine culture conditions as expected, such inhibition did not reverse PX resistance in PPSS conditions. Paradoxically, treatment with inhibitors in serum‐starved conditions produced an elevation of their respective target proteins. In addition, we found that Digitoxin, an FDA approved drug that decrease the viability of cancer cells growing under PPSS, downregulates the expression of Sox2, MDR1, phospho‐ AKT, Wnt5a/b, and β‐catenin. Our data suggest that PPSS‐induced chemoresistance is the result of extensive rewiring of intracellular signaling networks and that multi‐resistance can be effectively overcome by simultaneously targeting multiple targets of the rewired network. Furthermore, our PPSS model provides a simple and useful tool to screen drugs for their ability to target multiple pathways of cancer resistance. J. Cell. Physiol. 232: 2033–2043, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Cancer cells growing under prolonged periods of serum starvation (PPSS) become multidrug resistant. Under PPSS cancer cells respond aberrantly and paradoxically to some anticancer drugs likely by rewire signaling pathway networks.